α-decay half-lives new semi-empirical relationship including asymmetry, angular momentum and shell effects - Akrawy, Dashty T.; Poenaru, Dorin N.; Ahmed, Ali H.; Sihver, Lembit * (Elsevier, 2022)
We present a modified version of the semi-empirical formula SemFIS, which is based on the fission theory for predicting the alpha decay half-lives. The first version of SemFIS was found by D. N. Poenaru et al. and was at that time the best formula to predict the alpha-decay half-lives of superheavy nuclei among 18 different existing models. We compare a modified version of SemFIS against the old version and experimental data for four groups of alpha emitters: even-even; even-odd; odd-even, and odd-odd parent nuclei. Two sets of experimental values are used: set A, and set B. There are 356 nuclides in set A [137 e-e, 90 e-o, 66 o-e, and 63 o-o with Zmin, Zmax of (52,118); (52,112); (63,117), and (53,117), and Amin, Amax of (108,294); (107,281); (147,293), and (110,294), respectively]. Set B includes 420 α-emitters [144 e-e, 112 e-o, 84 o-e, and 80 o-o] with Zmin, Zmax of (52,118); (52,116); (53,117), and (53,117), and Amin, Amax of (106,294); (105,293);(111,293) and (110,294)]. Our study shows that the modified version of SemFIS gives better agreements with the experimental data than previously published versions.